RETRACTED: The Effects of Financial Development and Pandemics Prevalence on Forests: Evidence From Asia-Pacific Region - Wang, Jiajie; Khan, Yousaf Ali; Khodaei, Mehdi; Khezr, Somayeh; Karimi, Muhammad Sharif; Salem, Sultan (Frontiers in Environmental Science, 2022)
Achieving sustainable development and the necessity to pay attention to the quality of the environment is one of the challenges of the new century. Experimental studies on deforestation determinants have focused mainly on analyzing an environmental Kuznets curve for deforestation (EKCd). The present study introduces three contributions to experimental studies using data from 15 Asia-Pacific countries over a sixteen-year period, from 2005 to 2020. In this regard, the effects of six financial development indexes and a new pandemic uncertainty index on forest regions have been investigated. Moreover, the effects of the variables have been estimated through a spatial econometric model. This estimation can be used to investigate the variables of neighboring countries on the inland forest cover of countries. Diagnostic tests confirmed the spatial Durbin model. The results indicate the existence of an environmental Kuznets curve hypothesis. The trade openness variable has decreased the inland forest cover; however, the trade openness in neighboring countries has increased the inland forest cover in the countries. Besides, similar results were obtained for urbanization. Furthermore, natural resource rent is a beneficial factor dominating the improvement of forest areas. As confirmed by the results, the financial institution depth has a significant adverse effect on the forest cover of countries. The results for other reductions in financial development are meaningless. Despite the theoretically positive and negative dimensions of pandemics, the estimation results highlight its positive effects in forest regions.